1998
DOI: 10.1046/j.1365-8711.1998.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Hipparcos observations of pre-main-sequence stars

Abstract: We present first results of Hipparcos observations of nearby low‐mass pre‐main‐sequence (PMS) stars (T Tauri and Herbig Ae/Be stars). The data obtained by Hipparcos allow us to derive weighted mean parallaxes for three major nearby star‐forming regions (SFRs), Lupus, Chamaeleon I and Taurus–Auriga. Furthermore, results on the isolated objects AB Dor and TW Hya are presented. Finally, we discuss the evolutionary status of Herbig Ae/Be (HAEBE) stars on the basis of Hipparcos results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 14 publications
13
163
0
Order By: Relevance
“…Krautter 1991 andHughes et al 1993 for a discussion). The Hipparcos measurements of the T Tauri stars in Lupus confirms this result with 145 ± 50 pc mean distance (see Wichmann et al 1998 for T Tauri stars known before the ROSAT mission and Neuhäuser & Brandner 1998 for T Tauri stars newly found by the ROSAT mission). However, some members of Lupus also appeared to be as far as ∼ 190 pc (Wichmann et al 1998), while Knude & Hog (1998) Nakajima et al (2000) give ∼ 150 pc for Lupus; Franco (2002) argues for ∼ 150 pc as the most probable distance to the dark cloud known as Lupus I;and Sartori et al (2003) specify 147 pc.…”
Section: The Common Proper Motion Pairsupporting
confidence: 67%
“…Krautter 1991 andHughes et al 1993 for a discussion). The Hipparcos measurements of the T Tauri stars in Lupus confirms this result with 145 ± 50 pc mean distance (see Wichmann et al 1998 for T Tauri stars known before the ROSAT mission and Neuhäuser & Brandner 1998 for T Tauri stars newly found by the ROSAT mission). However, some members of Lupus also appeared to be as far as ∼ 190 pc (Wichmann et al 1998), while Knude & Hog (1998) Nakajima et al (2000) give ∼ 150 pc for Lupus; Franco (2002) argues for ∼ 150 pc as the most probable distance to the dark cloud known as Lupus I;and Sartori et al (2003) specify 147 pc.…”
Section: The Common Proper Motion Pairsupporting
confidence: 67%
“…The Taurus star-formation region has a distance of ≈ 140 pc (Kenyon et al 1994;Wichmann et al 1998;Torres et al 2012) and extends over a region of one hundred square degrees on the sky. The age of its population is ≈ 1 − 2 Myr, but Daemgen et al (2015) found an additional co-moving sub-population of ≈ 20 Myr.…”
Section: The Stellar and Substellar Population Inmentioning
confidence: 99%
“…For this calculation we have assumed a distance of 136 +54 −30 pc for V410 Tau (Wichmann et al 1998); errors in the distance could affect fluxes by up to a factor of almost 2. In order to convert magnitudes into absolute fluxes, we used the table provided by Rydgren et al (1984) for the Johnson filters, and by Gray (1998) for the Strömgren filters.…”
Section: Photometric Monitoringmentioning
confidence: 99%